PKM PELATIHAN PENGGUNAAN KINESIO TAPE PADA PENANGANAN CEDERA SISWA SMPN 2 MAJENE - Darul Husnul; Iskandar Iskandar; Nurliani Nurliani (Program Studi Ilmu Keolahragaan, 2023)
Proper handling of injuries will have a positive impact on improving athlete performance in the future. Kinesio tape is believed to be able to restore the neuromuscular system to normal, relieve pain during exercise, accelerate the recovery of injuries to joint sites, and overcome inflammation under the skin. The provision of this training provides added value for partners which will be applied during matches so that the handling of injuries will be handled appropriately. Besides having amazing benefits, this kinesio tape also provides convenience to use. Made from 100 percent cotton and a combination of latex free materials, kinesio tape can make your movements more flexible. Another advantage of this kinesio tape is its ability to stick well, even when wet from sweat or water sports. That way this tool can be used in various fields of sports. This activity will be held for 3 days from 08.00 to 12.00 with the provision of materials related to a healthy lifestyle. The material filler is a team of sports injury experts from the Faculty of Sports Science, Makassar State University who are quite competent in providing material related to sports health.